Shifting the paradigm: unilateral infiltrates and ARDS?. Issue 6 (10th June 2021) - Torres, Antoni; Barbeta, Enric; Welte, Tobias
Acute respiratory distress syndrome (ARDS) may present in up to 10% of patients admitted to the intensive care unit and is associated with high mortality [1]. According to a prospective, international, and multicentre cohort conducted by LUNG SAFE investigators, patients with ARDS face a mortality that ranges from approximately 35% in mild cases to 46% in severe cases. Currently, the Berlin definition is the accepted definition and classification of ARDS [2]. The classification comprises severity stratification of ARDS per P aO2 / F IO2 (arterial oxygen tension to fraction of inspired oxygen) ratio by three categories: mild, moderate and severe. An imperative characteristic of the definition is the presence of bilateral infiltrates (not due to congestive heart failure, CHF) in a chest radiograph or computed tomography (CT) scan, and a positive end-expiratory pressure (PEEP) of at least 5 cmH2 O. Simple observation of chest radiograph quadrant involvement in ARDS could improve the prediction of mortality. Patients needing mechanical ventilation with unilateral and two quadrants chest radiograph involvement should receive protective ventilation. https://bit.ly/2KqwqVO